The implementation of listening and speaking learning using the integrated learning method in the faculty of language and culture UNTAG Semarang - Sogimin Sogimin; Gurendi Wiwoho (Universitas Aki, 2023)
ABSTRACT Teaching listening and speaking can be done by listening to audio, then assigning students to retell English. The author believes that listening teaching methods can be combined with speaking or other basic skills. This research reveals the application of listening and speaking teaching using the Integrated Learning method at the Faculty of Language and Culture, Semarang University, on August 17, 1945, and the obstacles faced in its application. The aim is to implement the integration of this method effectively, and in the future, it can be a reference for curriculum renewal according to the community's wishes. This research uses a research and development (R&D) design. Researchers collected data using listening tests and recordings of students' English speaking while listening to materials or tests. After that, the researcher conducted interviews with students as input for the application of this integration. The recordings were then transcribed and analyzed using a qualitative description. From the discussion, most of the students agreed with the application of integration, but a small number disagreed. From the experiment, the method of teaching the listening test combined with the English/speaking assignment in the first semester can be integrated or blended. The result will be that students' speaking abilities will be better and more effective because only 3 out of 20 students will answer only a few sentences that do not represent the content of the test. Two students answered in Bahasa Indonesia. Most of the others responded well.